Effects of the ARCS Instructional Model on Undergraduate Students’ Motivation and Learning Outcomes in an Online Basic Physics Course - Permadi, Dimas; Zakiya , Hanifah; Rahayu, Chika (Universitas Islam Negeri Ar-Raniry, 2026)
This study investigates the effectiveness of the ARCS motivational model (Attention, Relevance, Confidence, Satisfaction) in improving undergraduate students’ motivation and learning outcomes in an online Basic Physics course. A one‑shot case study design was employed with a single cohort of students (n = 37). Learning motivation was measured using a validated ARCS‑based questionnaire, while learning outcomes were assessed through a post‑test aligned with four Sub‑CPMK indicators. Descriptive statistics and the Wilcoxon signed‑rank test were used to analyze the data. The Wilcoxon test compared students’ post‑test scores against the predetermined minimum competency standard (KKM = 70). Results showed generally high levels of motivation across most indicators (61.95%–80.26%), although engaging learning activities fell within the moderate category (53.78%). Learning outcomes varied substantially, with the highest performance recorded in Sub‑CPMK 3 (analyzing motion through data, graphs, and equations) at 83.2%, and the lowest in Sub‑CPMK 2 (vector analysis and dipole moment concepts) at 14.6%. The Wilcoxon signed‑rank test yielded a significant result (p = 0.000), indicating that student performance significantly exceeded the KKM benchmark. These findings suggest that the ARCS model effectively enhances motivation and conceptual understanding, particularly for visually representable content, while highlighting the need for additional instructional scaffolding (e.g., progressive visual support and guided practice) to improve learning of abstract concepts such as vectors and dipole moments. Future research is recommended to employ stronger experimental controls (e.g., pretest‑posttest control group designs) and item‑level analyses to further validate the applicability of the ARCS model in online physics education.